Negative Pressure Wound Therapy: Mechanism of Action and Clinical Applications - Normandin, Shanel; Safran, Tyler; Winocour, Sebastian; Chu, Carrie K.; Vorstenbosch, Joshua; Murphy, Amanda M.; Davison, Peter G. (Seminars in Plastic Surgery, 2021)
Negative pressure wound therapy (NPWT) promotes healing by evenly applying negative pressure on the surface of the wound. The system consists of a sponge, a semiocclusive barrier, and a fluid collection system. Its effectiveness is explained by four main mechanisms of action, including macrodeformation of the tissues, drainage of extracellular inflammatory fluids, stabilization of the environment of the wound, and microdeformation. Rarely will complications linked to NPWT occur, but special care must be taken to prevent events such as toxic shock syndrome, fistulization, bleeding, and pain. New NPWT modalities have been recently developed to make NPWT suitable for a wider variety of wounds. These include NPWT with instillation therapy (NPWTi-d), different cleansing options, and application of NPWT on primarily closed incisions. Finally, vacuum-assisted wound closure therapy has been demonstrated to be efficient for various clinical settings, such as the management of diabetic foot ulcers, pressure ulcerations, chronic wounds, and skin grafts.
Keywords: negative pressure wound therapy; VAC; wounds; semiocclusive membrane